A comparative study on the efficiency of ozonation and coagulation–flocculation as pretreatment to activated carbon adsorption of biologically stabilized landfill leachate. (September 2015) - Oloibiri, Violet; Ufomba, Innocent; Chys, Michael; Audenaert, Wim T.M.; Demeestere, Kristof; Van Hulle, Stijn W.H.
Highlights: FeCl3 is more efficient than PACl in reduction of organic matter. Sludge from FeCl3 treatment has better settling characteristics than PACl. Ozonation improves the break through time and adsorption capacity of GAC for COD. Coagulation–flocculation/GAC performs better than ozonation/GAC in UVA254 removal. Abstract: The present work investigates the potential of coagulation–flocculation and ozonation to pretreat biologically stabilized landfill leachate before granular activated carbon (GAC) adsorption. Both iron (III) chloride (FeCl3 ) and polyaluminium chloride (PACl) are investigated as coagulants. Better organic matter removal is observed when leachate was treated with FeCl3 . At a dose of 1 mg FeCl3 /mg CODo (CODo : initial COD content), the COD and α 254 removal was 66% and 88%, respectively. Dosing 1 mg PACl/mg CODo resulted in 44% COD and 72% α 254 removal. The settle-ability of sludge generated by PACl leveled off at 252 mL/g, while a better settle-ability of 154 mL/g was obtained for FeCl3 after dosing 1 mg coagulant/mg CODo . For ozonation, the percentage of COD and α 254 removal increased as the initial COD concentration decreased. Respectively 44% COD and 77% α 254 removal was observed at 112 mg COD/L compared to 5% COD and 26% α 254 removal at 1846 mg COD/L. Subsequent activated carbon adsorption of ozonated, coagulated and untreated leachate resulted in 77%, 53% and 8% total COD removal after treatment of 6 bed volumes. Clearly showing the benefit of treating the leachate before GAC adsorption. Mathematical modeling of the experimental GAC adsorption data with Thomas and Yoon–Nelson models show that ozonation increases the adsorption capacity and breakthrough time of GAC by a factor of 2.5 compared to coagulation–flocculation.